Robust Bain distortion in the premartensite phase of a platinum-substituted Ni2MnGa magnetic shape memory alloy - Singh, S.; Dutta, B.; D'Souza, S.W.; Zavareh, M.G.; Devi, P.; Gibbs, A.S.; Hickel, T.; Chadov, S.; Felser, C.; Pandey, D. (Nature Publishing Group, 2017)
The premartensite phase of shape memory and magnetic shape memory alloys (MSMAs) is believed to be a precursor state of the martensite phase with preserved austenite phase symmetry. The thermodynamic stability of the premartensite phase and its relation to the martensitic phase is still an unresolved issue, even though it is critical to the understanding of the functional properties of MSMAs. We present here unambiguous evidence for macroscopic symmetry breaking leading to robust Bain distortion in the premartensite phase of 10% Pt-substituted Ni2MnGa. We show that the robust Bain-distorted premartensite (T2) phase results from another premartensite (T1) phase with preserved cubic-like symmetry through an isostructural phase transition. The T2 phase finally transforms to the martensite phase with additional Bain distortion on further cooling. Our results demonstrate that the premartensite phase should not be considered as a precursor state with the preserved symmetry of the cubic austenite phase. © 2017 The Author(s).
Keywords: Robust Bain distortion; premartensite phase; platinum-substituted; Ni2MnGa; magnetic shape memory alloy